YAP/TAZ in Bone and Cartilage Biology - Zarka, Mylène; Haÿ, Eric; Cohen-Solal, Martine (Frontiers in Cell and Developmental Biology, 2022)
YAP and TAZ were initially described as the main regulators of organ growth during development and more recently implicated in bone biology. YAP and TAZ are regulated by mechanical and cytoskeletal cues that lead to the control of cell fate in response to the cellular microenvironment. The mechanical component represents a major signal for bone tissue adaptation and remodelling, so YAP/TAZ are master orchestrators of bone and cartilage homeostasis. Recently, mice and cellular models have been developed to investigate the precise roles of YAP/TAZ in bone and cartilage cells, which appear to be crucial. This review provides an overview of YAP/TAZ regulation and function, notably providing new insights into the role of YAP/TAZ in bone biology.